Peran Sektor Pariwisata Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Sumba Timur - Virginio Y. L Ndjurumbaha; Maria I. H.Tiwu; Fransina W. Ballo (Universitas Kristen Indonesia Toraja, 2024)
Tourism has become the largest industry and shows consistent growth from year to year. This study aims to determine the role of the tourism sector in increasing local revenue. This research uses a qualitative approach, with data collection methods conducting interviews, observation, documentation. The results of this study indicate that the tourism sector plays a very important role in increasing local revenue which in turn can improve the welfare of the community around tourist sites and economic growth so that regional income occurs. But there are also obstacles from the tourism sector in increasing regional income, namely the lack of destinations that are managed directly by the tourism office so that of the existing destinations only 2 are included in the original regional income.